2020
DOI: 10.18280/ti-ijes.642-418
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Sustainability on an Industrial Case Within Industry 4.0 Paradigm: Advantages of Involving Exergetic Analysis in Life Cycle Thinking

Abstract: With the constant increase in energy costs and their impacts on environmental policies, optimizing production and reducing operating costs is considered a critical tactic for companies to remain globally competitive. In the height of the Industry 4.0 era, the need to digitize and automate manufacturing processes emerges as another predominant goal. The difficulty lies in understanding how thermodynamic laws can enhance energy efficiency and support for the strategies to approach the transformation into a smart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The processes leading to Industry 4.0 include the introduction of innovative technologies and their implementation in the educational process, as reflected in the works of Laciok et al (2020) and Marchenko et al (2023). Particular attention is paid to environmental sustainability and exergy analysis in the context of industrial production, as shown in a study by Selicati and Cardinale (2020). A key aspect is service innovation and the use of big data analytics, as explored by Lee et al (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The processes leading to Industry 4.0 include the introduction of innovative technologies and their implementation in the educational process, as reflected in the works of Laciok et al (2020) and Marchenko et al (2023). Particular attention is paid to environmental sustainability and exergy analysis in the context of industrial production, as shown in a study by Selicati and Cardinale (2020). A key aspect is service innovation and the use of big data analytics, as explored by Lee et al (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 1. LCA framework form [5] The ISO standards are based on a process-based LCA approach and are organized into four steps: goal and scope definition, inventory analysis, impact assessment, and interpretation as shown in Figure 1.…”
Section: Dealing With Sustainability In Manufacturing Through Exergy Life Cycle Assessment and Hybrid Approachesmentioning
confidence: 99%
“…Starting from the work carried out and published in the proceedings of the AIGE IIETA Congress on TI-IJES [1], the following paper is an extension and completion of the considerations and the analysis implemented in the paper.…”
Section: Introductionmentioning
confidence: 99%